THE NEUTRALITY TRAP: ASSESSING THE SUSTAINABILITY OF UZBEKISTAN’S GOLD-BACKED EXCHANGE RATE POLICY - Yakubov Jakhongir (European Science Publishing, 2025)
Since the liberalization of the foreign exchange market in 2017, the Central Bank of Uzbekistan (CBU) has operated under a "Principle of Neutrality"—selling foreign currency reserves only to sterilize the liquidity generated by domestic gold purchases. This paper analyzes the efficacy of this mechanism during the volatility of 2024–2025. By correlating gold price fluctuations with CBU intervention volumes, we demonstrate that the stability of the Uzbek Soum (UZS) has become structurally dependent on global gold markets rather than domestic productivity. While this "Gold-FX Shield" successfully limited depreciation to ~4.7% in 2024, our results suggest it creates a "Neutrality Trap," where a significant correction in gold prices would force the regulator to choose between abandoning neutrality or permitting a destabilizing currency shock.
Keywords: Gold–fx shield, principle of neutrality, foreign exchange market, central bank of uzbekistan, gold price volatility, currency intervention, exchange rate stability, neutrality trap, monetary policy, uzbek soum.